Fish Smoking Technology to Increase Income of the "Sentono Ing Nyawiji" Catfish Cultivation Group, In Janget Hamlet, Morang Village, Kare District, Madiun Regency - East Java - Andrew Joewono; Adriana Anteng Anggorowati; Ivan Gunawan; Hartono Pranjoto; Dyna Rachmawati (Jurnal Syntax Transformation, 2024)
One of the MBKM programs is building villages, so the proposer applies science, technology, soft-skills and hard-skills to collaborate with partners to build villages. The theme chosen is food. Partner problems: (1). how to increase income from cultivating catfish which has a profit of under 10% to be greater than 40%. By using processing technology from catfish cultivation to produce products that are different from the general ones (fresh catfish). Catfish is processed into smoked catfish which is packaged and ready to be marketed. This has a positive impact, with an increase in income from the cultivation of catfish, into processed smoked catfish from the technology of processing catfish harvests using smoking. The solution to this problem is to make a fish smoker. The output is a multi-story fish smoker fueled by coconut fiber which functions to dry or preserve harvested catfish by providing space heating using smoke from the burnt fuel. The next problem, (2). how do partners have financial management skills, so that partners can run a sustainable catfish processing business, to increase income from the catfish cultivation business, including by marketing their products. As a continuation, it is hoped that catfish farming partners can advance to become MSMEs. The solution is to be given training in using financial governance with the SI APIK application from Bank Indonesia. The output of partner empowerment is being able to record bookkeeping and every financial transaction. The SI APIK application can be useful for small-scale individual businesses.